ANALISIS PENGARUH EFEKTIVITAS MEDIA TEKNOLOGI TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMKIT NURUL ILMI - Rina Indah Pertiwi; Siti Annisa; Siti Nur Halizah; Sri Bulan Cahyani; Tri Maulana Putra; Wildan Ahmad (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The rapid development of information and communication technology has significantly impacted the transformation of the education sector, particularly in the methods of delivering content and learning strategies. One major application of technology in education is the use of instructional media to create more engaging, efficient, and meaningful learning processes. In the era of Education 4.0, which emphasizes technological integration and student-centered learning, instructional media such as audio and audio-visual formats play a crucial role in enhancing student engagement and stimulating multiple senses simultaneously. These media can present information in a concrete and contextual manner, facilitating better understanding of the material. Furthermore, the teacher’s role has shifted from being the primary source of information to becoming a facilitator who provides and manages learning resources according to students’ needs. In this context, educational technology serves not only as a teaching aid but also as a scientific and strategic approach that supports learning effectiveness and efficiency.